Prevalence of Hepatitis B Surface Antigen and Anti-hepatitis B Core Antibodies among Blood Donors in Diyala-Iraq - Hadeel M. Fayyadh (Journal of Global Pharma Technology, 2016)
Background: In Diyala province and since 2014, the anti-hepatitis B core antibodies (Anti-HBc Abs) was introduced beside the hepatitis B surface antigen (HBsAg) as seromarkers for blood donation screening to reduce the residual risk of occult hepatitis B infection (OHBI). Objectives: this is a lookback study to explore the efficiency of HBc Abs versus HBsAg seromarkers in reducing the residual risk of OHBI through blood transfusion in Diyala province. Materials and methods: This follow-up study starting in January 2016 to August 2017. The results of HBsAg and anti-HBc Abs as blood units screening seromarkers were followed and abstracted from the records of the Central Blood Bank in Diyala Directory of Health. Simple statistical analysis was done using SPSS Version 18 and P value was considered significant wherever it is below 0.05. Results: The results found that the total number of blood units donated during the follow-up period was 47258. The total HBV positive was 2423 (5.12%), of which 213 (0.45%) were HBsAg positive and 2210 (4.67%) were anti-HBc total antibody positive. Totally, 2369 (5.012%) blood donors were positive for both markers. All the 213 blood donors who were positive for HBsAg recorded throughout the two years were male (100%). Whereas 2145 (99.48%) and 11 (0.51%) blood donors positive for anti-HBc Ab were male and female respectively. Cumulatively, 2358 (99.53%) males and 11 (0.46 %) female were positive for both HBV markers. Conclusion: The introduction of anti-HBc Ab along with HBs Ag for screening of blood units is remarkably increase the number of blood units with positive HBV infection and consequently improve the blood safety.Keywords: HBsAg, Anti-HBc Ab, Blood safety, Diyala.